Low temperature photoresponse of monolayer tungsten disulphide - Cao, Bingchen (2014)
High photoresponse can be achieved in monolayers of transition metal dichalcogenides. However, the response times are inconveniently limited by defects. Here, we report low temperature photoresponse of monolayer tungsten disulphide prepared by exfoliation and chemical vapour deposition (CVD) method. The exfoliated device exhibits n-type behaviour; while the CVD device exhibits intrinsic behaviour. In off state, the CVD device has four times larger ratio of photoresponse for laser on/off and photoresponse decay–rise times are 0.1 s (limited by our setup), while the exfoliated device has few seconds. These findings are discussed in terms of charge trapping and localization.